Pengaruh Pupuk Hayati dan Briket Amelioran terhadap Pertumbuhan Tanaman Padi pada Tanah Salin - Mieke Rochimi Setiawati; Syifa Nabila Kurnia; Pirda Nurhopipah; Anas Ramdhani; Pujawati Suryatmana; Diyan Herdiyantoro; Tualar Simarmata; Betty Natalie Fitriatin (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2023)
Utilization of saline land as an effort to increase rice productivity is still constrained by the adverse effects of salinity stress. The solution to this effort can be done by utilizing PGPR biofertilizers and applying ameliorant briquettes. The purpose of this study was to evaluate the effect of using biofertilizers and ameliorant briquettes on saline soils with various levels of salinity on the growth of rice plants. This research was conducted at the Ciparanje Jatinangor screen house from September 2022 to January 2023. The research design used was a randomized block design with 12 treatments and 3 replications. The treatment applied was PGPR biofertilizer, ameliorant briquettes, and their combination on saline soil 4 and 8 dS m-1 compared to control (non-saline soil). The results showed that PGPR biofertilizer increased the height of rice plants on saline soils 4 and 8 dS m-1 7 DAP. At 14 DAP, PGPR biofertilizer, ameliorant briquettes, and their combinations did not increase rice plant height, root length and volume, wet weight, and dry weight of rice plants, although the application of biofertilizers, ameliorant briquettes, and their combinations tended to increase wet weight and dry weight of rice plant compared to soil with the same salinity without biofertilizers and ameliorant briquettes.